Do I trust you when you smile?: Effects of sex and emotional expression on facial trustworthiness appraisal - Galinsky, Dina F.; Erol, Ezgi; Atanasova, Konstantina; Bohus, Martin; Krause-Utz, Annegret; Lis, Stefanie (PLOS ONE, 2020)
Background Trust is a prerequisite for successful social relations. People tend to form a first impression of people‘s trustworthiness based on their facial appearance. The sex of the judging person and its congruency with the sex of the judged people influence these appraisals. Moreover, trustworthiness and happiness share some facial features, which has led to studies investigating the interplay between both social judgments. Studies revealed high correlation in judging happiness and trustworthiness across different facial identities. However, studies are missing that investigate whether this relationship exists on a within-subject level and whether in-group biases such as the congruency between the sex of the judging and judged individual influence this relationship. In the present study, we addressed these questions. Methods Data were collected in an online-survey in two separate samples (N = 30, German sample, N = 107 Dutch sample). Subjects assessed the intensity of happiness and trustworthiness expressed in neutral and calm facial expression of the same characters (50% males, 50% females). Statistical analyses comprised rm-Anova designs based on rating scores and estimates of within-subject associations between both judgments. Results Our findings replicate high correlations between happiness and trustworthiness ratings across facial identities based on average scores across participants. However, the strength of this association was strongly dependent on the methodological approach and inter-subject variability was high. Our data revealed an in-group advantage for trustworthiness in women. Moreover, the faces’ sex and emotional expressions differentially influenced the within-subject correlation between both judgments in men and women. Conclusion Our findings replicate previous studies on the association between happiness and trustworthiness judgments. We extend our understanding of the link between both social judgments by uncovering that within-subject variability is high and influenced by sex and the availability and appraisal of positive emotional facial cues.